IMPLEMENTASI AUGMENTED REALITY PENCARIAN KATEGORI BUKU RAK PERPUSTAKAAN BERBASIS MOBILE - Amanda Ghina Nur Rahmayanti; Adam Sekti Aji (Politeknik Bisnis Indonesia, 2023)
This research aims to build an Augmented reality application that can display book category information and short descriptions in the form of 3D objects. When borrowing books at the library, new visitors often have difficulty finding the book they are looking for, which has an impact on the length of the book search process. This research was built with structured stages starting from problem identification to testing. This AR application will later be installed on the smartphone. This system will later be able to help library members find books to borrow or read by directing their smartphones to the book categories on the shelves. The findings from this research show that the LibraryAR application was successfully built and tested to determine the quality of the markers using Vuforia, which shows that the markers have a high rating value. Apart from that, testing was also carried out to determine the optimal distance for the markers to be detected, where all markers were successfully detected up to a distance of 50 cm. Based on these results, it shows that the LibraryAR application can be used to simplify and speed up the book search process.